A Survey of Online Learning during Pandemic Covid-19 by Teacher of English of Junior High School in Malang - Muhammad irfan Nashiruddin Afif (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: Online learning is one method in the learning process without meeting or face to face, so the student can learn from home or everywhere. Moreover, nowadays, many sectors use English like industry, education, and medical and so on. Since there is a coronavirus the activities should be done at home to avoid the virus. Meanwhile, doing online learning is not easy because there are some factors faced by teachers such as facilities, technology literacy, and learning methods. Those factors indicated that the teacher has problems in using media in teaching English to their students. This project is a quantitative study using a survey research design. Finally, this study aims to find out the teacher's perception of online learning during pandemic COVID-19. The second one is to investigate the factors affecting online learning, and the last is to know the teacher's competency in using media for online learning. The subjects of this study were English teachers of junior high school in Malang. The researcher took the subject from a group of MGMP (Musyawarah Guru Mata Pelajaran) of Malang. The total number of the English teachers of junior high school was 45 from school around Malang. The data collected using a questionnaire. The data analysis was done by calculating.The result of this research showed that the teachers have positive perception about online learning during pandemic Covid-19, they also think that media learning is effective for students and teachers to keep them healthy from the virus. However, lack of teacher’s competence, internet data, and personal characteristics are the factor that can affect online learning. The teachers can use the media of learning online.keywords: covid-19, online laearning, and english teacher